Новые виды морских червей сипункулид (Sipuncula) рода Phascolosoma - Мурина, В.В. (Вестник зоологии, 1975)
Three new species of the genus Phascolosoma: Ph. (Rueppellisoma) golikovi Murina, Ph. (Phascolosoma) riukiuensis Murina and Ph. (Antillesoma) schmidti Murina, were described from Prof. P. Schmidt's collections from the Ruykyu Islands and A. Golikov's collections from the Sea of Japan.